OPPORTUNITIES AND TECHNOLOGIES FOR PREPARING FUTURE TEACHERS OF FINE ARTS FOR THE FORMATION OF ELEMENTS OF ARTISTIC THINKING IN SCHOOLCHILDREN (Academia Science Repository, 2023)
Indicators such as the fact that future teachers of Fine Arts conduct negaroruk research on the formation of elements of artistic thinking in schoolchildren, know ways to improve their skills, plan methodological and negaroruk work in this area are also an important factor in assessing the level of readiness for professional-negaroruk activities. The article explores the possibilities and technologies for preparing future teachers of Fine Arts for the formation of elements of artistic thinking in schoolchildren.